Typology of Fatwā Documented by Prohibition of Sadd al-Dharāyi‘ (Evasive Legal Devices) in Imāmiya Jurists’ Supposition - ?????, ????; ????? ????, ????; ?????, ???? (???????? ??????? ?????? ????)
The validity of sad al-dharāyi‘ (evasive legal devices) is among the age-old controversial problems of jurisprudence and principles of jurisprudence of legal schools. In the meantime, the Imāmī jurists have had a negative approach in methodology of Islamic jurisprudence (‘ilm al-uṣūl) toward its validity. What is noteworthy is that irrespective of the uṣūlī viewpoints of the Imāmī jurists, we find instances from among their fatwas that by way of causal inference in them they seem to be one of the referents of sadd al-dharāyi‘ and this indicates the non-homogeneity of the uṣūlī and jurisprudential viewpoints of the Imāmī jurists in the problem in question. Despite similar designations such as unlawful premise in Imāmīya’s principles of jurisprudence, the existing discrepancy can be a totally verbal dispute and resolve no difference between them in practice. The present article is intended to enumerate the jurisprudential evidences and referents in respect to its claim and tries to find sadd al-dharāyi‘ as applicable to them by way of causal inference in these referents.